(untitled) (Global Journal of Management and Business Research, 2018)
Social media, a new dimension of marketing promotion mix, has made it possible for users to express their views about the companies, as well as their advertising. The purpose of this study was to test four hypotheses regarding the effects of young social media users’ attitude, behavioral response, and purchasing intention toward social media advertising in South Asian perspective. The study selected four popular social networking sites such as Facebook, Twitter, YouTube and Google Plus which indicated the highest Asian visitor and surveyed with a structured questionnaire, asking respondents to mention their attitudinal views and responses about social media and social media advertising. The result identifies variation in predictors of users’ buying decision and provides some indications for using and developing social media platform for advertisement in the developing country and describes how to reach more user response in a regular time frame with the ultimate success of purchasing goal.